Landscape and the visual hermeneutics of place, 1500-1700 (Leiden ; Boston)
xxxiii, 579 sayfa
Keywords: “This volume examines the image-based methods of interpretation that pictorial and literary landscapists employed between 1500 and 1700. The seventeen essays ask how landscape, construed as the description of place in image and/or text, more than merely inviting close viewing, was often seen to call for interpretation or, better, for the application of a method or principle of interpretation.“ --